Deliberative Democracy and the Three Inputs of Governance: Expertise, Self-Interest, and Emotions - Michał Zabdyr-Jamróz; Elena Popa (Politeja)
The idea of evidence-based policy-making is in crisis. On the one hand, it is being disrupted by agonistic partisan polarization and post-truth politics. On the other hand, despite some nostalgia for technocracy, converging trends in political science and theory downplay the authoritative role of expertise, while emotions and self-interest receive positive reappraisals. This is most clearly visible in the evolution of deliberative democratic theory. In order to synthesize these developments, we present an integrated framework of the three inputs of governance: expertise, self-interest and emotions. We discuss and systematize nondeliberative and deliberative ways of considering these three inputs. The latter include: meaningful and contextualized representation of expertise; deliberative negotiation on parties’ self-interests; as well as emotional testimonies, storytelling, bridging rhetoric etc. The framework highlights the composite nature of political discourse (as an interplay between the three inputs), serving as a comprehensive tool for policy analysis and a guide for institutional design.